1997
DOI: 10.1111/j.1432-1033.1997.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Proteoglycan Decorin Transient 2‐Phosphorylation of Xylose during Formation of the Trisaccharide Linkage Region

Abstract: Phosphorylation of decorin was investigated by incubating a rat fibroblast cell line with radiolabelled phosphate and carbohydrate precursors. There was a transient phosphorylation of the linkage-region saccharides in intracellular decorin prior to assembly of the galactosaminoglycan chain. Phosphorylation gradually increased from xylosylated, galactosyl-xylosylated to galactosyl-galactosyl-xylosylated core protein where all trisaccharide stubs were phosphorylated. Addition of the first glucuronate residue was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 24 publications
5
43
1
2
Order By: Relevance
“…These results sug-gest that phosphorylation of the Xyl residue takes place after transfer of the first Gal residue by GalT-I and before transfer of the GlcUA residue by GlcAT-I. Indeed, phosphorylation of the Xyl residue is most prominent after the addition of two Gal residues (11,12). Transient phosphorylation of Xyl residues seems to enhance the formation of the linkage region (13)(14)(15).…”
mentioning
confidence: 67%
“…These results sug-gest that phosphorylation of the Xyl residue takes place after transfer of the first Gal residue by GalT-I and before transfer of the GlcUA residue by GlcAT-I. Indeed, phosphorylation of the Xyl residue is most prominent after the addition of two Gal residues (11,12). Transient phosphorylation of Xyl residues seems to enhance the formation of the linkage region (13)(14)(15).…”
mentioning
confidence: 67%
“…These modifications show a rather wide distribution in various tissues of many different vertebrate species. 2-O-Phosphorylation of Xyl has been found for CS from shark cartilage (13), rat (40) and mouse (12) tumors, and for CS/DS from rat fibroblast cell line (41). It was also found for HS/Hep from bovine lung (10, 42).…”
Section: Discussionmentioning
confidence: 88%
“…Fransson and his co-workers (41,53,54) have reported that the phosphorylation of Xyl is a transient phenomenon and is not inhibited by brefeldin A, which interferes with progression from the endoplasmic reticulum to Golgi. They have also found in the early steps of the CS chain biosynthesis of decorin that the degree of phosphorylation increases to ϳ90% until the linkage region grows into the Gal-Gal-Xyl trisaccharide, and then dephosphorylation takes places extensively accompanied by glucuronidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent simultaneous analysis of both CS and HS chains of the hybrid type proteoglycan syndecan-1 molecule has suggested the Xyl phosphorylation of both CS and HS chains (34). Structural analysis of the biosynthetic intermediate oligosaccharides formed in the cultured rat fibroblasts has suggested that dephosphorylation takes place soon after the transfer reaction of GlcUA to the trisaccharide (57)(58)(59). In vitro enzyme assays using crystallized human glucuronyltransferase I as enzyme (60) and Gal-Gal-Xyl(2-O-phosphate)-Ser as acceptor have demonstrated the higher enzyme activity with the phosphorylated acceptor substrate.…”
Section: Disaccharidesmentioning
confidence: 99%